Vocabulary Development - Rasinski, Timothy (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Knowledge of word meanings is critical to success in reading. A reader cannot fully understand a text in which the meaning to a significant number of words is unknown. Vocabulary knowledge has long been correlated with proficiency in reading. Yet, national surveys of student vocabulary knowledge have demonstrated that student growth in vocabulary has been stagnant at best. This volume offers new insights into vocabulary knowledge and vocabulary teaching. Articles range from a presentation of theories of vocabulary that guide instruction to innovative methods and approaches for teaching vocabulary. Special emphasis is placed on teaching academic and disciplinary vocabulary that is critical to success in content area learning. Our hope for this volume is that it may spark a renewed interest in research into vocabulary and vocabulary instruction and move toward making vocabulary instruction an even more integral part of all literacy and disciplinary instruction.